Patterns and Dynamics of SST Fronts in the California Current System. Issue 2 (15th February 2020) - Mauzole, Y. L.; Torres, H. S.; Fu, L.‐L.
Abstract: The California Current System (CCS) is one of the four major Eastern Boundary Current Systems, where major coastal upwelling is observed in the ocean. Oceanic fronts are abundant in the CCS, and are known to be associated with coastal upwelling. Analyses of satellite observations (altimetry and sea surface temperature, SST) of the CCS highlight the presence of SST fronts in the southern part of the CCS outside of the coastal upwelling season, which will be investigated. The submesoscale‐permitting and tidal‐resolving LLC4320‐simulation was used to analyze the nature of these features, through the study of the surface density gradients, the vertical velocities and the horizontal strain. An algorithm was also developed to track SST fronts in the model. The classical scenario of coastal upwelling is confirmed in the central CCS (off California), with a strain field correlated to vertical velocities associated with the SST fronts, and collocated density fronts. In contrast, in the southern CCS (off Baja California), vertical velocities were much weaker and density gradients were not always observed where SST fronts were detected, leading to the assumption that the fronts there may be affected by thermohaline compensation occurring in the region. These findings confirm the existence of SST fronts in the CCS outside of the traditional coastal upwelling framework, with part of the fronts in the southern CCS being passive and advected by the background flow. Plain Language Summary: Oceanic fronts can be defined as narrow boundaries separating waters with distinct properties (such as temperature) and play a major role in fisheries and marine ecology. This is particularly true for some of the features observed in the California Current System, which spans the western coast of North America. Indeed, fronts off California are due to a process called coastal upwelling, resulting in the presence of fronts that act as oases for marine life. Combined satellite observations of the region highlight the presence of temperature fronts off Baja California, which appear to have different patterns than the fronts off California. The aim of this paper is to investigate the nature of the temperature fronts found off Baja California, and to understand their distinct dynamics. Because satellite observations are confined to the ocean surface, we rely on a high‐resolution numerical simulation to study the three‐dimensional dynamics of the fronts. Our results show that some of the temperature fronts observed off Baja California, behave in a passive manner, in contrast with the fronts off California: they are not associated with coastal upwelling and are mainly carried out by the background flow. The implications for the local marine ecosystem remained to be clarified. Key Points: Sea surface height and sea surface temperature data reveal two distinctive frontal patterns across the California Current System Simulations by an ocean model highlight various frontal patterns in the California Current System Dynamically passive fronts dominate off Baja California, whereas dynamically active fronts dominate off California